Diagnosis of cystic fibrosis in London and South East England before and after the introduction of newborn screening. Issue 3 (15th November 2013) - Lim, MTC; Wallis, C; Price, J F; Carr, S B; Chavasse, R J; Shankar, A; Seddon, P; Balfour-Lynn, I M
Abstract : Introduction: Newborn screening (NBS) for cystic fibrosis (CF) was introduced to London and South East England in 2007. We wished to assess the details of missed cases, and to compare the age at diagnosis and other clinical parameters, prescreening and postscreening. Methods: Retrospective and prospective case notes and database review of all newly diagnosed CF patients in our 7 CF centres, for 18 months before and 4 years after NBS started. Results: 347 patients were diagnosed with CF. 126 patients were not screened (born before or abroad), and had a median age at diagnosis of 2.4 years, excluding those with meconium ileus (MI). Their median time to diagnosis from initial symptoms was 1 year, and in 10% it was >6 years. After NBS started, 170 were diagnosed by NBS (48% were already symptomatic); 7 moved into the region after NBS elsewhere; 34 presented with MI (6 were negative on NBS); and 10 screened children were missed (false negative cases). Median age of diagnosis was 3 weeks. Prevalence was 1 in 3991 live births. By 2 years of age (with data on 104 patients), 49 children (47%) had their first isolation of Pseudomonas aeruginosa, while 37 (36%) had their first growth of Staphylococcus aureus from respiratory cultures. Conclusions: NBS has significantly reduced the age of diagnosis, although many were symptomatic even at 3 weeks of age. A small number of patients with CF can still be missed by the screening programme, and the diagnosis should be considered even with a negative screen result.